Alternative grading strategies in organic chemistry: a journey - Mio, Matthew J. (Frontiers in Education, 2024)
The global pandemic forced educators at all levels to re-evaluate how they would engage content, generate relevance, and assess the development of their students. While alternative grading strategies were not necessarily new to the world of chemical education research (CER) in 2020, the pandemic accelerated the examination of such principles for instructors who wished to prioritize learning over compliance 1 with course policies and eschew points for grading. This article describes the transformation of a traditional lecture organic chemistry course under new, standards-based principles. Working from a discrete set of grouped learning outcomes, these courses aim to clearly define standards, give helpful feedback, indicate semester-long student progress, and allow for reattempts without penalty using a token system. 2 Students explore both core (all of which must be passed in order to show progress) and non-core (students can choose a majority of these to pass) learning outcomes in a variety of formative and summative assessment approaches. Unique to the reformatting of these courses is the use of collaborative, take-home assessments, integration of multiple-choice questions, ungrading of student-submitted summary notes, 3 live solving of select problems with peer feedback, and a learning check system that reinforces the flipped nature of content delivery. Another distinctive feature of the courses is the requirement for students who reach a certain threshold of repeating learning outcomes to perform in-person problem solving for the instructor. 4 Overall, students report that the structure of the courses reduces their general and specific anxiety, lowers the temptations to challenge their academic integrity, and increases their own learning self-monitoring, reflecting known pedagogies of metacognition. 5 The instructor reports that alternative grading strategies take far less time, generates more meaningful feedback, and shifts student attitudes away from final grading and toward genuine learning.